Prevention of Vaginal SHIV Transmission in Macaques by a Coitally-Dependent Truvada Regimen - Radzio, Jessica; Aung, Wutyi; Holder, Angela; Martin, Amy; Sweeney, Elizabeth; Mitchell, James; Bachman, Shanon; Pau, Chou-Pong; Heneine, Walid; García-Lerma, J. Gerardo (PLOS ONE, 2012)
Background Daily pre-exposure prophylaxis (PrEP) with Truvada (a combination of emtricitabine (FTC) and tenofovir (TFV) disoproxil fumarate (TDF)) is a novel HIV prevention strategy recently found to prevent HIV transmission in men who have sex with men and heterosexual couples. We previously showed that a coitally-dependent Truvada regimen protected macaques against rectal SHIV transmission. Here we examined FTC and tenofovir TFV exposure in vaginal tissues after oral dosing and assessed if peri-coital Truvada also protects macaques against vaginal SHIV infection. Methods The pharmacokinetic profile of emtricitabine (FTC) and tenofovir (TFV) was evaluated at first dose. FTC and TFV levels were measured in blood plasma, rectal, and vaginal secretions. Intracellular concentrations of FTC-triphosphate (FTC-TP) and TFV-diphosphate (TFV-DP) were measured in PBMCs, rectal tissues, and vaginal tissues. Efficacy of Truvada in preventing vaginal SHIV infection was assessed using a repeat-exposure vaginal SHIV transmission model consisting of weekly exposures to low doses of SHIV162p3. Six pigtail macaques with normal menstrual cycles received Truvada 24 h before and 2 h after each weekly virus exposure and six received placebo. Infection was monitored by serology and PCR amplification of SHIV RNA and DNA. Results As in humans, the concentration of FTC was higher than the concentration of TFV in vaginal secretions. Also as in humans, TFV levels in vaginal secretions were lower than in rectal secretions. Intracellular TFV-DP concentrations were also lower in vaginal tissues than in rectal tissues. Despite the low vaginal TFV exposure, all six treated macaques were protected from infection after 18 exposures or 4 full menstrual cycles. In contrast, all 6 control animals were infected. Conclusions We modeled a peri-coital regimen with two doses of Truvada and showed that it fully protected macaques from repeated SHIV exposures. Our results open the possibility for simplified PrEP regimens to prevent vaginal HIV transmission in women.